Impact of Demographic and Lifestyle Factors on Irritable Bowel Syndrome from Basra - Mansour, Zahraa Saad; Mahdi, Dawood S.; Alsaimary, Ihsan Edan (Journal of Biomedicine and Biochemistry, 2025)
Background Irritable Bowel Syndrome (IBS) is a common functional gastrointestinal disorder affecting quality of life. Despite its prevalence, its pathophysiology remains unclear, necessitating further investigation into contributing factors. Objective The objective of this study is to identify the demographic characteristics and lifestyle factors associated with IBS in a population attending Basra Hospital. This will enhance our understanding of the condition and inform potential management strategies. Materials and Methods A cross-sectional study was conducted in- volving patients diagnosed with IBS at Al-Sadr Teaching Hospital and Al- Fayhaa Teaching Hospital in Basra/Iraq. Participants completed a struc- tured questionnaire assessing demographic information, lifestyle habits (di- etary patterns, smoking, and exercise), and psychological stress. Data were analyzed using statistical analysis performed using Microsoft Office Excel 2013 and GraphPad Prism 9.2.0.software to determine correlations between factors and IBS prevalence. Results Preliminary findings indicate that women are disproportion- ately affected by IBS compared to men, with significant associations ob- served between IBS symptoms and dietary habits, particularly the con- sumption of high-fat and low-fiber foods. Psychological stress was also identified as a critical factor influencing symptom severity. Conclusion This study highlights the importance of demographic and lifestyle factors in understanding IBS. Targeting these elements may lead to improved management strategies and enhanced patient outcomes. Further research is necessary to explore the complex interplay of these factors in the pathophysiology of IBS.